Necesidad de reformar el código de policía marítima para la aplicación legal de la convención de las naciones unidas sobre el derecho del mar Convemar. - DUCHI JIMBO, GEOVANNY ISRAEL (2011)
In this research, an analysis of Ecuadorian maritime navigation, in the process of evolution of the law of the sea, application and limitations, until reaching its institutionalization in the year of 1982, at the third United Nations Conference on the right to the sea, where specific encoding with normative nature on the sea, called the Convention on the law of the sea issues (UNCLOS), which entered into full force in 1994. This becomes, in short, the new era of the law of the sea hosted by much of coastal and not coastal countries around the world On the basis of this institutional framework, it is of vital importance analysis of the implications of the possible accession of the Ecuador to the United Nations Convention on the law of the Sea (UNCLOS), and the impacts that would be the same on sovereignty and delimitation of maritime spaces Finally, analyze the proposed a legal reform to police maritime code updating monetary amounts with respect to fines and penalties, view that police maritime services, aim to needs humanitarian and public interest attached to the administrative and functional structures of public order and public safety.